Understanding Racial/Ethnic Diversity Gaps Among Early Career Teachers. (May 2019) - Redding, Christopher; Baker, Dominique J.
The growing evidence on the importance of teacher representation points to the need to better understand the factors shaping the lack of racial/ethnic diversity in the teacher workforce. In this study, we examine the extent to which college major choice explains racial/ethnic gaps in teaching. Drawing on data from the Baccalaureate and Beyond Longitudinal Study, we find that White college graduates are close to twice as likely to major in education compared to Black, Latinx, and other graduates of color. Even among college graduates, respondents who identify as White are 5 percentage points more likely to enter teaching than respondents who identify as Black and 2 percentage points more likely to enter teaching than graduates who identify as Latinx. Regression and decomposition analyses demonstrate that the observed racial/ethnic gaps in entry to teaching can largely be explained by whether a graduate studied education in college.